PEMANFAATAN BUKTI-BUKTI TRANSAKSI RUMAH TANGGA SEBAGAI MEDIA PEMBELAJARAN MATA KULIAH MANAJEMEN KEUANGAN DAN PRAKTEK AKUNTANSI PADA PROGRAM STUDI PENDIDIKAN AKUNTANSI FKIP UNIVERSITAS PGRI PALEMBANG - Zahruddin; Septi Yuniarti (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2017)
This reseacrh entitled “the use of invoice household transaction as financial management instructional media in accounting education study program, faculty of teacher training and education, PGRI University of Palembang” which aims to find out the effect of invoice household transaction as instructional media to improve the students learning outcomes for financial management subjects and accounting practice. The output of this research skim were teaching materials or national proceedings. The design of this study was an experimental research. The population concist of all of the fifth semester of financial management students (59 persons) and all of the seventh semester of accounting practice students (79 persons). By using clustered random sampling technique, the fifth class A and the seventh class A were chosen to be the experimental class. While, the fifth class B and the seventh class B were chosen to be the control class. Data was collected by way of documentation and test. Data analysis used t test, through prerequisite test with normality test and homogeinity test used SPPS 21. The result showed that there was a significant effect of the use invoice household transaction as instructional media for financial management students learning outcome (Sig. (2-tailed) 0,001< 0,05). There was also similiar result with the use invoice household transaction as instructional media for accounting practice student learning outcome (Sig. (2-tailed) and Z. Asymp. Sig. (2-tailed) 0,000 < 0,05, Z value 4.783 > 1,96 ).